Reading the Nation: Migration as a Generative Theme - Leah Durán (WOW Stories)
Paulo Freire, a foundational figure in field of literacy, introduced the idea that reading the word always also involves reading the world (Freire & Macedo, 2005). In Freire’s work in adult education, “reading the world” was often accomplished through the use of generative themes, in which the words that students first learned were based on important aspects of their social, cultural and political worlds. These topics or themes were characterized as “generative” in that they contained the possibility not only for learning to read and write but also for thinking critically and expansively about the structures of their everyday lives. In this article, I draw on this concept to show how migration served as a generative theme for our work with teachers in a two-week NEH Summer Institute for K-12 teachers.